Anti-smashing industrial and mining protective boot and preparation process thereof

CN119529397APending Publication Date: 2025-02-28ANHUI GUANHONG PLASTIC IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411763443.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-28

Smart Images

  • Figure BDA0005168262180000021
    Figure BDA0005168262180000021
  • Figure BDA0005168262180000031
    Figure BDA0005168262180000031
  • Figure BDA0005168262180000032
    Figure BDA0005168262180000032
Patent Text Reader

Abstract

The invention discloses an anti-smashing industrial and mining protective boot, and belongs to the technical field of protective boots, the industrial and mining protective boot comprises the following raw materials by weight: 60.2-70.5 parts of thermoplastic styrene butadiene rubber, 20.3-28.7 parts of modified polystyrene resin, 15.3-20.6 parts of modified carbon fiber, 2.6-3.4 parts of a plasticizer, 4.5-5.7 parts of paraffin, and 1.5-5.6 parts of stearic acid; the invention further discloses a preparation process of the mining protective boot. Organic-inorganic materials are compounded, so that the puncture resistance of the protective boot is enhanced, the modified carbon fibers have good mechanical properties and high strength, the impact resistance is greatly enhanced, the phenomenon that toes are kicked by foreign objects or bruised or crushed by falling foreign objects in the walking process is effectively avoided, the safety is high, and the protective boot is worthy of popularization and application. And the modified polystyrene resin is added, so that the protective boots are endowed with excellent ultraviolet resistance, and the anti-aging performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of protective boots, and relates to an industrial and mining protective boot for preventing and resisting smashing and a preparation process thereof. Background Art

[0002] Protective boots are special boots with protective functions. They can protect workers from various dangerous factors during the production process. They mainly protect against possible injuries to the foot, toes, soles and other injuries. Protective boots can be divided into: toe protection safety shoes, anti-puncture shoes, anti-static shoes, conductive shoes, electrical insulation shoes, oil-resistant protective boots, and heat-resistant boots according to their functions.

[0003] Referring to Chinese patent CN111700342A, a wear-resistant and highly comfortable mining boot is disclosed, comprising a sole, a toe, an upper and a boot shaft; the upper and the sole are composed of two layers of colloid protective layers and a waterproof cloth layer located between the two layers of colloid protective layers, and the colloid protective layers located on the inner sides of the upper and the sole are provided with spaced air holes; the mining boots provided by the invention have a sole made of a blended system of butadiene rubber and butadiene rubber / PVC blended rubber, and a composite filling system of carbon black and zinc oxide is introduced into the blended system to improve the wear resistance of the sole of the mining boots, but due to the use of the blended system of butadiene rubber and butadiene rubber / PVC blended rubber, the rubber is corroded by ultraviolet rays after long-term use, and the aging is serious, which greatly shortens the service life of the protective boots, causing economic losses and waste of resources. Summary of the invention

[0004] The object of the present invention is to provide an anti-smashing and anti-smashing industrial and mining protective boot and a preparation process thereof, so as to solve the problems involved in the background technology.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A kind of industrial and mining protective boots for anti-smashing and anti-smashing, comprising the following raw materials in parts by weight:

[0007] 60.2-70.5 parts of thermoplastic styrene-butadiene rubber, 20.3-28.7 parts of modified polystyrene resin, 15.3-20.6 parts of modified carbon fiber, 2.6-3.4 parts of plasticizer, 4.5-5.7 parts of paraffin wax, and 1.5-5.6 parts of stearic acid;

[0008] The industrial and mining protective boots are prepared by the following steps:

[0009] Step A1: adding paraffin wax and stearic acid into a pulverizer for pulverization, passing through a 200-300 mesh sieve, and mixing to obtain a mixed powder;

[0010] Step A2: After mixing the thermoplastic styrene-butadiene rubber, modified polystyrene resin and mixed powder at 150-160° C. for 30-40 minutes, adding the modified carbon fiber and plasticizer and continuing mixing for 1-1.5 hours to obtain a rubber material;

[0011] Step A3: Add the rubber material into the mold, perform compression molding at 150-160° C., and then cool to obtain industrial and mining protective boots.

[0012] Furthermore, the plasticizer in step A2 is one or more of dioctyl phthalate, diethyl phthalate, and dibutyl phthalate mixed in any proportion.

[0013] The modified polystyrene resin is prepared by the following steps:

[0014] Step S1, add 2,4-dihydroxybenzophenone and anhydrous ethanol to a three-necked flask, add 2 mol / L sodium hydroxide solution and dimethyl sulfate dropwise thereto under an ice bath, stir and react at room temperature for 12 hours, filter, wash the filter cake with deionized water and 90% ethanol solution for 2-3 times, respectively, and then place in an oven at 60-65° C. and dry for 5-6 hours to obtain intermediate 1;

[0015] The reaction process is as follows:

[0016]

[0017] Step S2, add POC 1 into the three-necked flask 3 , DMF was slowly added dropwise in an ice bath, reacted for 20-25 min, and then the DMF solution of intermediate 1 was added dropwise thereto, the temperature was raised to 75°C and reacted for 5-6 h, and then poured into ice water after cooling, and neutralized to neutrality with saturated sodium carbonate solution, filtered, and the filter cake was washed with deionized water for 2-3 times, and then recrystallized with anhydrous ethanol to obtain intermediate 2;

[0018] The reaction process is as follows:

[0019]

[0020] Step S3, add AlCl into the three-necked flask 3 , intermediate 2, dichloromethane, introduce nitrogen, stir the reaction at room temperature for 4 hours, pour into ice water, add 50% by mass hydrochloric acid solution to adjust the pH to 5.2-5.5, stand and separate, wash the organic phase with saturated brine, add 40% by mass sodium hydroxide solution to adjust the pH to 8.5-9, stand and separate, add 1 mol / L hydrochloric acid solution to the aqueous phase until solid precipitates, filter, wash the filter cake with deionized water 2-3 times, and then dry it in an oven at 60-65°C for 5-6 hours to obtain intermediate 3;

[0021] The reaction process is as follows:

[0022]

[0023] Step S4, adding 98% by mass concentrated sulfuric acid, deionized water and p-chloro-o-nitroaniline into a three-necked flask, stirring evenly, cooling to 0-5° C., adding 40% by mass sodium nitrite solution dropwise thereto, and reflux reaction for 1-2 hours to obtain intermediate 4;

[0024] The reaction process is as follows:

[0025]

[0026] Step S5, add deionized water, intermediate 3, and sodium hydroxide to a three-necked flask, cool to 0-5°C, add intermediate 4, keep warm for 2-3 hours, add 40% hydrochloric acid solution to neutralize, filter, wash the filter cake with deionized water 2-3 times, and then dry at 60-70°C for 3-4 hours to obtain intermediate 5;

[0027] The reaction process is as follows:

[0028]

[0029] Step S6, add intermediate 5, deionized water, 95% ethanol solution and sodium hydroxide into a three-necked flask, stir evenly, add sodium dithionite, heat to 80-90°C and reflux for 2-3h, pour the product into ice water to precipitate, add 30% hydrochloric acid solution to adjust the pH to 5-6, obtain a white emulsion, filter, wash the filter cake with 95% ethanol solution for 2-3 times, dry at 60-70°C for 4-5h, and obtain intermediate 6;

[0030] The reaction process is as follows:

[0031]

[0032] Step S7, adding ethyltriphenylphosphonium bromide into a three-necked flask, introducing nitrogen, adding anhydrous tetrahydrofuran, adding dropwise 1.3 mol / L n-butyllithium solution at -78°C, stirring at room temperature for 1 hour, then lowering the temperature to -78°C, adding dropwise a tetrahydrofuran solution of intermediate 6, continuing stirring at room temperature for 12 hours, pouring the reaction solution into n-hexane, standing for 2 hours, filtering to remove the precipitate, rotating the filtrate to dryness, and then recrystallizing from n-propanol to obtain intermediate 7;

[0033] The reaction process is as follows:

[0034]

[0035] Step S8, melt-blending polystyrene, intermediate 7 and azobisisobutyronitrile at 200-240° C. and then extruding and granulating to obtain modified polystyrene resin.

[0036] The reaction process is as follows:

[0037]

[0038] Furthermore, in step S1, the usage ratio of 2,4-dihydroxybenzophenone, anhydrous ethanol, sodium hydroxide solution and dimethyl sulfate is 0.11-0.14 mol: 90-100 mL: 120-125 mL: 0.33-0.42 mol.

[0039] Further, the POC 1 in step S2 3 The usage ratio of DMF and intermediate 1 in the DMF solution of intermediate 1 is 50.2-50.5 mmol:4.8-5.1 mL:4.7-4.8 mL, and the usage ratio of DMF and intermediate 1 in the DMF solution of intermediate 1 is 5 mL:40.1-40.3 mmol.

[0040] Further, in step S3, A l C l 3 , intermediate 2, and dichloromethane are used in a dosage ratio of 15.1-15.5 mmol: 5.2-5.4 mmol: 15-17 mL.

[0041] Furthermore, the usage ratio of the concentrated sulfuric acid, deionized water, p-chloro-o-nitroaniline and sodium nitrite solution in step S4 is 25.5-25.7 g: 35-40 mL: 17.1-17.5 g: 18.1-18.5 g.

[0042] Furthermore, in step S5, the usage ratio of deionized water, intermediate 3, sodium hydroxide and intermediate 4 is 100-105 mL: 23.5-23.8 g: 38.1-38.4 g: 18.5-18.7 g.

[0043] Furthermore, in step S6, the usage ratio of the intermediate 5, deionized water, ethanol solution, sodium hydroxide, and sodium dithionite is 25.5-26 g: 140-150 mL: 140-150 mL: 35-40 g: 41.5-42.3 g.

[0044] Furthermore, in step S7, the dosage ratio of ethyltriphenylphosphonium bromide, anhydrous tetrahydrofuran, n-butyllithium solution, and tetrahydrofuran solution of intermediate 6 is 10.2-10.5 mmol: 40.2-40.8 mL: 7.5-7.8 mL: 19.8-20.5 mL, and the dosage ratio of tetrahydrofuran and intermediate 6 in the tetrahydrofuran solution of intermediate 6 is 20 mL: 7.1-7.4 mmol.

[0045] Furthermore, the weight proportions of the polystyrene, intermediate 7 and azobisisobutyronitrile in step S8 are: 20.5-28.6 parts of polystyrene, 75.4-8.7 parts of intermediate and 0.08-0.2 parts of azobisisobutyronitrile.

[0046] The modified carbon fiber is prepared by the following steps:

[0047] Step C1, adding carbon fiber to acetone, heating to 70°C for 48 hours, then transferring to 40% by mass concentrated nitric acid for activation for 3-4 hours, washing with deionized water until neutral, and placing in a 60°C oven for drying for 20-23 hours to obtain activated carbon fiber;

[0048] Step C2, add activated carbon fiber and SOC l into a three-necked flask 2 , DMF, stir evenly, heat to 78 ° C to react for 48 hours, take out, wash and dry, put into ethylene glycol, heat to 80 ° C for 24 hours, and then place in a 60 ° C oven to dry for 10-15 hours to obtain hydroxyl-containing carbon fiber;

[0049] Step C3, add ethyl orthosilicate, deionized water and 45% ammonia water into a three-necked flask, stir evenly, react at room temperature for 5-6 hours, add KH-550 and continue to react for 1 hour, centrifuge, wash the precipitate with water 2-3 times, and then place it in a 60°C oven to dry for 5-8 hours to obtain amino silica;

[0050] Step C4, adding the hydroxyl-containing carbon fiber to DMF and ultrasonically dispersing it for 5-7 minutes, adding amino silicon dioxide, and ultrasonically dispersing it for 30-40 minutes, and then reacting it at 70° C. for 20-23 hours to obtain modified carbon fiber.

[0051] Furthermore, in step C1, the mass ratio of the carbon fiber, acetone and concentrated nitric acid is 1:10-15:12-16.

[0052] Further, the activated carbon fiber and SOC l in step C2 2 The usage ratio of DMF and ethylene glycol is 1.1-1.5g:20-30mL:1-2mL:20-30mL.

[0053] Furthermore, in step C3, the usage ratio of ethyl orthosilicate, deionized water, ammonia water, and KH-550 is 15-20 g: 12-15 g: 3-4 mL: 1.5-2 mL.

[0054] Furthermore, the usage ratio of the hydroxyl-containing carbon fiber, DMF, and amino-silica in step C4 is 0.5-0.8 g: 45-50 mL: 10-25 mg.

[0055] Beneficial effects of the invention: The purpose of the invention is to provide an anti-smash and anti-smash industrial and mining protective boots and a preparation process thereof. The raw materials of the industrial and mining protective boots include thermoplastic styrene-butadiene rubber, modified polystyrene resin, modified carbon fiber, etc., and the composite of organic-inorganic materials is adopted to enhance the puncture resistance of the protective boots, and the boots can be worn for a long time in special environments such as construction sites and mines. The modified carbon fiber has good mechanical properties and high strength, and greatly enhances the impact resistance, effectively avoiding the phenomenon of kicking foreign objects or being crushed or smashed by falling foreign objects during walking, and has high safety. The carbon fiber is modified to improve its compatibility with the polymer. First, the carbon fiber is washed to remove the sizing agent, and then the activated carbon fiber is subjected to a performance treatment, first with SOC l 2 The carbon fiber is reacted with ethylene glycol to obtain hydroxyl-containing carbon fiber, and then the surface amino silica sol is prepared by a sol-gel method. The surface amino silica sol is reacted with hydroxyl-containing carbon fiber to obtain surface-modified carbon fiber. The modified carbon fiber has better compatibility with thermoplastic styrene-butadiene rubber, modified polystyrene resin and other polymers, which is conducive to hydrogen bonding and interweaving more closely, thereby improving the integrity and greatly enhancing the mechanical properties.

[0056] Secondly, by adding modified polystyrene resin, the protective boots are also endowed with excellent UV resistance and anti-aging performance. First, 2,4-dihydroxybenzophenone reacts with dimethyl sulfate to generate intermediate 1, intermediate 1 introduces aldehyde group through Vilsmeier-Haack reaction to generate intermediate 2, intermediate 2 undergoes demethylation reaction to generate intermediate 3, then p-chloro-o-nitroaniline is reacted under acidic and sodium nitrite conditions to generate intermediate 4, intermediate 4 and intermediate 3 react under alkaline conditions to generate intermediate 5, intermediate 5 reacts under sodium dithionite conditions to generate intermediate 6 containing benzotriazole, intermediate 6 reacts with ethyltriphenylphosphonium bromide under the action of n-butyl lithium. ng reaction to generate intermediate 7. Under the action of initiator azobisisobutyronitrile, intermediate 7 is grafted onto the polystyrene molecular chain, so that the chain segment is connected with benzophenone and benzotriazole structures, showing excellent light stability and ultraviolet absorption ability, achieving the gain of ultraviolet absorption ability. The carbonyl group and hydroxyl group in the benzophenone molecule produce intramolecular hydrogen bonds to form a chelate ring. When the molecule is irradiated with ultraviolet light, it absorbs energy, the intramolecular hydrogen bonds are destroyed, the chelate ring opens, and the ultraviolet light energy is converted into heat energy and released. In addition, the carbonyl group in the molecule is excited to undergo isomerization, which also consumes part of the energy. In addition, benzotriazole has an effect on 30 Ultraviolet rays in the wavelength range of 0-385nm have a highly efficient absorption effect, and their absorption efficiency is high and their own stability is good. They convert the absorbed light energy into heat energy through tautomerism. Before absorbing ultraviolet rays, they exist in the form of phenolic compounds. The absorption of ultraviolet rays causes the electron density to move mainly from the oxygen atom to the nitrogen atom of the triazole ring. The nitrogen atom is alkaline, and the proton is quickly transferred to the nitrogen atom to form an unstable tautomer. The absorbed energy is then dissipated in the form of heat energy and returns to the ground state. Together with benzophenone, a synergistic effect is exerted, the ultraviolet absorption ability is more efficient, and the anti-aging ability is better, thereby extending the service life of the protective boots. DETAILED DESCRIPTION

[0057] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Example 1

[0059] The modified polystyrene resin is prepared by the following steps:

[0060] Step S1, add 0.11 mol 2,4-dihydroxybenzophenone and 90 mL anhydrous ethanol into a three-necked flask, add 120 mL 2 mol / L sodium hydroxide solution and 0.33 mol dimethyl sulfate dropwise thereto under an ice bath, stir and react at room temperature for 12 h, filter, wash the filter cake twice with deionized water and 90% ethanol solution by mass, respectively, and then dry in an oven at 60° C. for 5 h to obtain intermediate 1;

[0061] Step S2, add 50.2 mmol POC l into the three-necked flask 3 , 4.8 mL of DMF was slowly added dropwise in an ice bath, after reacting for 20 min, 4.7 mL of DMF solution of intermediate 1 was added dropwise thereto, the temperature was raised to 75 °C and reacted for 5 h, after cooling, poured into ice water, neutralized to neutrality with saturated sodium carbonate solution, filtered, the filter cake was washed twice with deionized water, and then recrystallized with anhydrous ethanol to obtain intermediate 2, wherein the amount ratio of DMF to intermediate 1 in the DMF solution of intermediate 1 was 5 mL:40.1 mmol;

[0062] Step S3, add 15.1 mmol Al Cl into the three-necked flask 3 , 5.2mmol intermediate 2, 15mL dichloromethane, introduce nitrogen, stir the reaction at room temperature for 4h, pour into ice water, add 50% hydrochloric acid solution by mass to adjust the pH to 5.2, let stand and separate, wash the organic phase with saturated brine, add 40% sodium hydroxide solution by mass to adjust the pH to 8.5, let stand and separate, add 1mol / L hydrochloric acid solution to the aqueous phase until solid precipitates, filter, wash the filter cake twice with deionized water, and then dry it in a 60℃ oven for 5h to obtain intermediate 3;

[0063] Step S4, add 25.5 g of 98% concentrated sulfuric acid, 35 mL of deionized water and 17.1 g of p-chloro-o-nitroaniline into a three-necked flask, stir evenly, cool to 0° C., add 18.1 g of 40% sodium nitrite solution dropwise thereto, and reflux for 1 h to obtain intermediate 4;

[0064] Step S5, add 100 mL of deionized water, 23.5 g of intermediate 3, and 38.1 g of sodium hydroxide into a three-necked flask, cool to 0°C, add 18.5 g of intermediate 4, keep warm for 2 hours, add 40% hydrochloric acid solution to neutralize, filter, wash the filter cake with deionized water twice, and then dry at 60°C for 3 hours to obtain intermediate 5;

[0065] Step S6, add 25.5g of intermediate 5, 140mL of deionized water, 140mL of 95% ethanol solution and 35g of sodium hydroxide into a three-necked flask, stir evenly, add 41.5g of sodium dithionite, heat to 80°C and reflux for 2h, pour the product into ice water to precipitate, add 30% hydrochloric acid solution to adjust the pH to 5, obtain a white emulsion, filter, wash the filter cake twice with 95% ethanol solution, and dry at 60°C for 4h to obtain intermediate 6;

[0066] Step S7, adding 10.2 mmol ethyltriphenylphosphonium bromide into a three-necked flask, introducing nitrogen, adding 40.2 mL anhydrous tetrahydrofuran, adding dropwise 7.5 mL 1.3 mol / L n-butyl lithium solution at -78 ° C, stirring at room temperature for 1 hour, then lowering the temperature to -78 ° C, adding dropwise 19.8 mL tetrahydrofuran solution of intermediate 6, continuing stirring at room temperature for 12 hours, pouring the reaction solution into n-hexane, standing for 2 hours, filtering to remove the precipitate, rotating the filtrate to dryness, and then recrystallizing from n-propanol to obtain intermediate 7, wherein the amount ratio of tetrahydrofuran to intermediate 6 in the tetrahydrofuran solution of intermediate 6 is 20 mL:7.1 mmol;

[0067] Step S8, melt-blending 20.5 parts of polystyrene, 5.4 parts of intermediate 7, and 0.08 parts of azobisisobutyronitrile at 200° C. and then extruding and granulating to obtain a modified polystyrene resin.

[0068] Example 2

[0069] The modified polystyrene resin is prepared by the following steps:

[0070] Step S1, add 0.12 mol 2,4-dihydroxybenzophenone and 95 mL anhydrous ethanol into a three-necked flask, add 123 mL 2 mol / L sodium hydroxide solution and 0.36 mol dimethyl sulfate dropwise thereto under an ice bath, stir and react at room temperature for 12 h, filter, wash the filter cake twice with deionized water and 90% ethanol solution by mass, respectively, and then dry in an oven at 62° C. for 5 h to obtain intermediate 1;

[0071] Step S2, add 50.3 mmol POC l into the three-necked flask 3 , 4.9 mL of DMF was slowly added dropwise in an ice bath, after reacting for 23 min, 4.7 mL of DMF solution of intermediate 1 was added dropwise thereto, the temperature was raised to 75 °C and reacted for 5 h, after cooling, poured into ice water, neutralized to neutrality with saturated sodium carbonate solution, filtered, the filter cake was washed twice with deionized water, and then recrystallized with anhydrous ethanol to obtain intermediate 2, wherein the amount ratio of DMF to intermediate 1 in the DMF solution of intermediate 1 was 5 mL:40.2 mmol;

[0072] Step S3, add 15.3 mmol Al Cl into the three-necked flask 3 , 5.3mmol intermediate 2, 16mL dichloromethane, introduce nitrogen, stir the reaction at room temperature for 4h, pour into ice water, add 50% hydrochloric acid solution by mass to adjust the pH to 5.3, stand and separate, wash the organic phase with saturated brine, add 40% sodium hydroxide solution by mass to adjust the pH to 8.8, stand and separate, add 1mol / L hydrochloric acid solution to the aqueous phase until solid precipitates, filter, wash the filter cake twice with deionized water, and then dry it in a 63℃ oven for 5h to obtain intermediate 3;

[0073] Step S4, add 25.6 g of 98% concentrated sulfuric acid, 37 mL of deionized water and 17.3 g of p-chloro-o-nitroaniline into a three-necked flask, stir evenly, cool to 3° C., add 18.3 g of 40% sodium nitrite solution dropwise thereto, and reflux for 1 h to obtain intermediate 4;

[0074] Step S5, add 103 mL of deionized water, 23.7 g of intermediate 3, and 38.2 g of sodium hydroxide into a three-necked flask, cool to 3°C, add 18.6 g of intermediate 4, keep warm for 2 hours, add 40% hydrochloric acid solution to neutralize, filter, wash the filter cake with deionized water twice, and then dry at 65°C for 3 hours to obtain intermediate 5;

[0075] Step S6, add 25.7g of intermediate 5, 145mL of deionized water, 145mL of 95% ethanol solution and 37g of sodium hydroxide into a three-necked flask, stir evenly, add 41.9g of sodium dithionite, heat to 85°C and reflux for 2h, pour the product into ice water to precipitate, add 30% hydrochloric acid solution to adjust the pH to 5, obtain a white emulsion, filter, wash the filter cake twice with 95% ethanol solution, and dry at 65°C for 4h to obtain intermediate 6;

[0076] Step S7, adding 10.3 mmol ethyltriphenylphosphonium bromide into a three-necked flask, introducing nitrogen, adding 40.5 mL anhydrous tetrahydrofuran, adding dropwise 7.6 mL 1.3 mol / L n-butyllithium solution at -78 ° C, stirring at room temperature for 1 hour, then lowering the temperature to -78 ° C, adding dropwise 20.2 mL tetrahydrofuran solution of intermediate 6, continuing stirring at room temperature for 12 hours, pouring the reaction solution into n-hexane, standing for 2 hours, filtering to remove the precipitate, rotating the filtrate to dryness, and then recrystallizing with n-propanol to obtain intermediate 7, wherein the amount ratio of tetrahydrofuran to intermediate 6 in the tetrahydrofuran solution of intermediate 6 is 20 mL:7.3 mmol;

[0077] Step S8, melt-blending 24.2 parts of polystyrene, 6.9 parts of intermediate 7, and 0.12 parts of azobisisobutyronitrile at 220° C. and then extruding and granulating to obtain a modified polystyrene resin.

[0078] Example 3

[0079] The modified polystyrene resin is prepared by the following steps:

[0080] Step S1, add 0.14 mol 2,4-dihydroxybenzophenone and 100 mL anhydrous ethanol into a three-necked flask, add 125 mL 2 mol / L sodium hydroxide solution and 0.42 mol dimethyl sulfate dropwise thereto under ice bath, stir and react at room temperature for 12 h, filter, wash the filter cake with deionized water and 90% ethanol solution for 3 times, respectively, and then dry in an oven at 65°C for 6 h to obtain intermediate 1;

[0081] Step S2, add 50.5 mmol POC l into the three-necked flask 3 , 5.1 mL of DMF was slowly added dropwise in an ice bath, after reacting for 25 min, 4.8 mL of DMF solution of intermediate 1 was added dropwise thereto, the temperature was raised to 75 °C and reacted for 6 h, after cooling, poured into ice water, neutralized to neutrality with saturated sodium carbonate solution, filtered, the filter cake was washed with deionized water for 3 times, and then recrystallized with anhydrous ethanol to obtain intermediate 2, wherein the amount ratio of DMF to intermediate 1 in the DMF solution of intermediate 1 was 5 mL:40.3 mmol;

[0082] Step S3, add 15.5 mmol Al Cl into the three-necked flask 3 , 5.4mmol intermediate 2, 17mL dichloromethane, introduce nitrogen, stir the reaction at room temperature for 4h, pour into ice water, add 50% hydrochloric acid solution by mass to adjust the pH to 5.5, stand and separate, wash the organic phase with saturated brine, add 40% sodium hydroxide solution by mass to adjust the pH to 9, stand and separate, add 1mol / L hydrochloric acid solution to the aqueous phase until solid precipitates, filter, wash the filter cake with deionized water 3 times, and then dry it in a 65℃ oven for 6h to obtain intermediate 3;

[0083] Step S4, add 25.7 g of 98% concentrated sulfuric acid, 40 mL of deionized water and 17.5 g of p-chloro-o-nitroaniline into a three-necked flask, stir evenly, cool to 5° C., add 18.5 g of 40% sodium nitrite solution dropwise thereto, and reflux for 2 h to obtain intermediate 4;

[0084] Step S5, add 105 mL of deionized water, 23.8 g of intermediate 3, and 38.4 g of sodium hydroxide into a three-necked flask, cool to 5°C, add 18.7 g of intermediate 4, keep warm for 3 hours, add 40% hydrochloric acid solution to neutralize, filter, wash the filter cake with deionized water 3 times, and then dry at 70°C for 4 hours to obtain intermediate 5;

[0085] Step S6, add 26g of intermediate 5, 150mL of deionized water, 150mL of 95% ethanol solution and 40g of sodium hydroxide into a three-necked flask, stir evenly, add 42.3g of sodium dithionite, heat to 90°C and reflux for 3h, pour the product into ice water to precipitate, add 30% hydrochloric acid solution to adjust the pH to 6, obtain a white emulsion, filter, wash the filter cake with 95% ethanol solution 3 times, and dry at 70°C for 5h to obtain intermediate 6;

[0086] Step S7, adding 10.5 mmol ethyltriphenylphosphonium bromide into a three-necked flask, introducing nitrogen, adding 40.8 mL anhydrous tetrahydrofuran, adding dropwise 7.8 mL 1.3 mol / L n-butyl lithium solution at -78 ° C, stirring at room temperature for 1 hour, then lowering the temperature to -78 ° C, adding dropwise 20.5 mL tetrahydrofuran solution of intermediate 6, continuing stirring at room temperature for 12 hours, pouring the reaction solution into n-hexane, standing for 2 hours, filtering to remove the precipitate, rotating the filtrate to dryness, and then recrystallizing with n-propanol to obtain intermediate 7, wherein the amount ratio of tetrahydrofuran to intermediate 6 in the tetrahydrofuran solution of intermediate 6 is 20 mL:7.4 mmol;

[0087] Step S8, melt-blending 8.6 parts of polystyrene, 8.7 parts of intermediate 7, and 0.2 parts of azobisisobutyronitrile at 240° C. and then extruding and granulating to obtain a modified polystyrene resin.

[0088] Example 4

[0089] The modified carbon fiber is prepared by the following steps:

[0090] Step C1, adding carbon fiber to acetone, heating to 70°C for 48 hours, then transferring to 40% by mass concentrated nitric acid for activation for 3 hours, washing with deionized water until neutral, and placing in a 60°C oven for drying for 20 hours to obtain activated carbon fiber, wherein the mass ratio of carbon fiber, acetone, and concentrated nitric acid is 1:10:12;

[0091] Step C2: Add 1.1 g activated carbon fiber and 20 mL SOC l into a three-necked flask. 2, 1mL DMF, stir evenly, heat to 78℃, react for 48h, take out, wash and dry, put into 20mL ethylene glycol, heat to 80℃, treat for 24h, and then place in a 60℃ oven to dry for 10h to obtain hydroxyl-containing carbon fiber;

[0092] Step C3, add 15g of tetraethyl orthosilicate, 12g of deionized water and 3mL of 45% ammonia water into a three-necked flask, stir evenly, react at room temperature for 5h, add 1.5mL of KH-550 and continue to react for 1h, centrifuge, wash the precipitate with water twice, and then dry it in an oven at 60°C for 5h to obtain amino silica;

[0093] Step C4, adding 0.5 g of hydroxyl-containing carbon fiber to 45 mL of DMF and ultrasonically dispersing for 5 min, adding 10 mg of amino-modified silica, ultrasonically dispersing for 30 min, and then reacting at 70° C. for 20 h to obtain modified carbon fiber.

[0094] Example 5

[0095] The modified carbon fiber is prepared by the following steps:

[0096] Step C1, adding carbon fiber to acetone, heating to 70°C for 48 hours, then transferring to 40% by mass concentrated nitric acid for activation for 3 hours, washing with deionized water until neutral, and drying in a 60°C oven for 21 hours to obtain activated carbon fiber, wherein the mass ratio of carbon fiber, acetone, and concentrated nitric acid is 1:13:14;

[0097] Step C2, add 1.3 g activated carbon fiber and 25 mL SOC l into a three-necked flask. 2 , 1mL DMF, stir evenly, heat to 78℃, react for 48h, take out, wash and dry, put into 25mL ethylene glycol, heat to 80℃, treat for 24h, and then place in a 60℃ oven to dry for 13h to obtain hydroxyl-containing carbon fiber;

[0098] Step C3, add 17g of ethyl orthosilicate, 13g of deionized water and 3mL of 45% ammonia water into a three-necked flask, stir evenly, react at room temperature for 5h, add 1.5mL of KH-550 and continue to react for 1h, centrifuge, wash the precipitate with water twice, and then dry it in an oven at 60°C for 5h to obtain amino silica;

[0099] Step C4, adding 0.6 g of hydroxyl-containing carbon fiber to 47 mL of DMF and ultrasonically dispersing for 6 min, adding 18 mg of amino silica, ultrasonically dispersing for 35 min, and then reacting at 70° C. for 21 h to obtain modified carbon fiber.

[0100] Example 6

[0101] The modified carbon fiber is prepared by the following steps:

[0102] Step C1, adding carbon fiber to acetone, heating to 70°C for 48 hours, then transferring to 40% by mass concentrated nitric acid for activation for 4 hours, washing with deionized water until neutral, and placing in a 60°C oven for drying for 23 hours to obtain activated carbon fiber, wherein the mass ratio of carbon fiber, acetone, and concentrated nitric acid is 1:15:16;

[0103] Step C2: Add 1.5 g activated carbon fiber and 30 mL SOC l into a three-necked flask. 2 , 2mL DMF, stir evenly, heat to 78℃, react for 48h, take out, wash and dry, put into 30mL ethylene glycol, heat to 80℃, treat for 24h, and then place in a 60℃ oven to dry for 15h to obtain hydroxyl-containing carbon fiber;

[0104] Step C3, add 20g of ethyl orthosilicate, 15g of deionized water and 4mL of 45% ammonia water into a three-necked flask, stir evenly, react at room temperature for 6h, add 2mL of KH-550 and continue to react for 1h, centrifuge, wash the precipitate with water 3 times, and then place it in a 60°C oven to dry for 8h to obtain amino silica;

[0105] Step C4, adding 0.8 g of hydroxyl-containing carbon fiber to 50 mL of DMF and ultrasonically dispersing for 7 min, adding 25 mg of amino-silica, ultrasonically dispersing for 40 min, and then reacting at 70° C. for 23 h to obtain modified carbon fiber.

[0106] Example 7

[0107] A kind of industrial and mining protective boots for anti-smashing and anti-smashing, comprising the following raw materials in parts by weight:

[0108] 60.2 parts of thermoplastic styrene-butadiene rubber, 20.3 parts of modified polystyrene resin, 15.3 parts of modified carbon fiber, 2.6 parts of dioctyl phthalate, 4.5 parts of paraffin wax, and 1.5 parts of stearic acid;

[0109] The industrial and mining protective boots are prepared by the following steps:

[0110] Step A1: adding paraffin wax and stearic acid into a grinder for grinding, passing through a 200-mesh sieve, and mixing to obtain a mixed powder;

[0111] Step A2: After mixing the thermoplastic styrene-butadiene rubber, the modified polystyrene resin prepared in Example 1 and the mixed powder at 150° C. for 30 minutes, the modified carbon fiber prepared in Example 4 and dioctyl phthalate were added and mixed for 1 hour to obtain a rubber material;

[0112] Step A3: Add the rubber material into the mold, perform compression molding at 150° C., and then cool to obtain industrial and mining protective boots.

[0113] Example 8

[0114] A kind of industrial and mining protective boots for anti-smashing and anti-smashing, comprising the following raw materials in parts by weight:

[0115] 65 parts of thermoplastic styrene-butadiene rubber, 24.5 parts of modified polystyrene resin, 17.4 parts of modified carbon fiber, 2.9 parts of diethyl phthalate, 5.1 parts of paraffin wax, and 3.3 parts of stearic acid;

[0116] The industrial and mining protective boots are prepared by the following steps:

[0117] Step A1: adding paraffin wax and stearic acid into a grinder for grinding, passing through a 250-mesh sieve, and mixing to obtain a mixed powder;

[0118] Step A2: After mixing the thermoplastic styrene-butadiene rubber, the modified polystyrene resin prepared in Example 2 and the mixed powder at 155° C. for 35 minutes, the modified carbon fiber prepared in Example 5 and diethyl phthalate were added and mixed for 1 hour to obtain a rubber material;

[0119] Step A3: Add the rubber material into the mold, perform compression molding at 155° C., and then cool to obtain industrial and mining protective boots.

[0120] Example 9

[0121] A kind of industrial and mining protective boots for anti-smashing and anti-smashing, comprising the following raw materials in parts by weight:

[0122] 70.5 parts of thermoplastic styrene-butadiene rubber, 28.7 parts of modified polystyrene resin, 20.6 parts of modified carbon fiber, 3.4 parts of dibutyl phthalate, 5.7 parts of paraffin wax, and 5.6 parts of stearic acid;

[0123] The industrial and mining protective boots are prepared by the following steps:

[0124] Step A1: adding paraffin wax and stearic acid into a grinder for grinding, passing through a 300-mesh sieve, and mixing to obtain a mixed powder;

[0125] Step A2: After mixing the thermoplastic styrene-butadiene rubber, the modified polystyrene resin prepared in Example 3 and the mixed powder at 160° C. for 40 minutes, the modified carbon fiber prepared in Example 6 and dibutyl phthalate were added and mixed for 1.5 hours to obtain a rubber material;

[0126] Step A3: Add the rubber material into the mold, perform compression molding at 160° C., and then cool to obtain industrial and mining protective boots.

[0127] Comparative Example 1

[0128] Industrial and mining protective boots produced by Guangzhou Juchenjian Protective Products Co., Ltd.

[0129] Comparative Example 2

[0130] The preparation method of the protective boots of Comparative Example 2 refers to Example 7, except that no modified carbon fiber is added.

[0131] Comparative Example 3

[0132] The preparation method of the protective boots of Comparative Example 3 refers to that of Example 7, except that no modified polystyrene resin is added.

[0133] The protective boots obtained in Examples 7-9 and Comparative Examples 1-3 were subjected to the following performance tests: (1) Anti-smashing performance: GB16756-5.4.3 (An1 type: impact hammer mass 23 kg, drop height 900 mm, after inspection, the deformation gap in the toe box is greater than 15 mm, which is qualified) was used to test the anti-smashing performance of the sole and the upper; (2) Anti-aging performance: an artificial accelerated aging test was carried out in accordance with GB / T 16422.2-1999 using a xenon arc lamp aging test chamber, with a relative spectral irradiance of 0.5 W / (m 2 ·nm), the test time is 1200h, the black standard thermometer temperature is 65℃, the box temperature is 40℃, the relative humidity is 50%, the spray cycle: spray 18min, stop 102min, the test data are shown in Table 1:

[0134] Table 1

[0135]

[0136]

[0137] It can be seen from Table 1 that, compared with Comparative Examples 1-3, the protective boots of Examples 7-9 not only have anti-smashing and anti-smashing properties and high safety, but also have anti-aging properties.

[0138] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0139] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A kind of industrial and mining protective boots for anti-smashing and anti-smashing, characterized in that: The invention comprises the following raw materials in parts by weight: 60.2-70.5 parts of thermoplastic styrene-butadiene rubber, 20.3-28.7 parts of modified polystyrene resin, 15.3-20.6 parts of modified carbon fiber, 2.6-3.4 parts of plasticizer, 4.5-5.7 parts of paraffin wax and 1.5-5.6 parts of stearic acid; The modified polystyrene resin is prepared by the following steps: polystyrene, intermediate 7 and azobisisobutyronitrile are melt-blended at 200-240° C. and then extruded and granulated to obtain the modified polystyrene resin.

2. The anti-smashing and anti-smashing industrial and mining protective boots according to claim 1 are characterized by: The weight proportions of the raw materials in preparing the modified polystyrene resin are as follows: 20.5-28.6 parts of polystyrene, 75.4-8.7 parts of the intermediate, and 0.08-0.2 parts of azobisisobutyronitrile.

3. The anti-smashing and anti-smashing industrial and mining protective boots according to claim 1 are characterized by: Intermediate 7 was prepared by the following steps: Step S1, add 2,4-dihydroxybenzophenone and anhydrous ethanol into a three-necked flask, add sodium hydroxide solution and dimethyl sulfate dropwise thereto under ice bath, stir and react at room temperature for 12 hours, filter with suction, wash and dry the filter cake to obtain intermediate 1; Step S2, add POCl3 to a three-necked flask, add DMF dropwise in an ice bath, react for 20-25 min, then add a DMF solution of intermediate 1 dropwise thereto, heat to 75°C and react for 5-6 h, cool and pour into ice water, neutralize with saturated sodium carbonate solution to neutrality, filter, wash and recrystallize the filter cake to obtain intermediate 2; Step S3, add AlCl3, intermediate 2, and dichloromethane to a three-necked flask, introduce nitrogen, stir the reaction at room temperature for 4 hours, pour into ice water, add hydrochloric acid solution to adjust the pH to 5.2-5.5, stand and separate, wash the organic phase with saturated brine, add sodium hydroxide solution to adjust the pH to 8.5-9, stand and separate, add hydrochloric acid solution to the aqueous phase until solid precipitates, filter with suction, wash and dry the filter cake to obtain intermediate 3; Step S4, after the concentrated sulfuric acid, deionized water and p-chloro-o-nitroaniline are uniformly stirred, the temperature is lowered to 0-5° C., a sodium nitrite solution is added dropwise thereto, and the mixture is refluxed for 1-2 hours to obtain an intermediate 4; Step S5, add deionized water, intermediate 3, and sodium hydroxide to a three-necked flask, cool to 0-5°C, add intermediate 4, keep warm for 2-3h, add hydrochloric acid solution to neutralize, filter, wash and dry the filter cake to obtain intermediate 5; Step S6, after the intermediate 5, deionized water, ethanol solution and sodium hydroxide are uniformly stirred, sodium dithionite is added, the temperature is raised to 80-90°C and refluxed for 2-3h, the product is poured into ice water to precipitate, and then hydrochloric acid solution is added thereto to adjust the pH to 5-6, and the product is filtered, and the filter cake is washed and dried to obtain the intermediate 6; Step S7, add ethyltriphenylphosphonium bromide into a three-necked flask, pass nitrogen, add anhydrous tetrahydrofuran, add n-butyllithium solution dropwise at -78°C, stir at room temperature for 1 hour, then lower the temperature to -78°C, add tetrahydrofuran solution of intermediate 6 dropwise, stir at room temperature for 12 hours, pour the reaction solution into n-hexane, let stand for 2 hours, filter to remove the precipitate, spin-dry the filtrate, and then recrystallize with n-propanol to obtain intermediate 7.

4. The preparation process of the anti-smashing and anti-smashing industrial and mining protective boots according to claim 1 is characterized in that: The method comprises the following preparation steps: Step A1: adding paraffin wax and stearic acid into a pulverizer for pulverization, passing through a 200-300 mesh sieve, and mixing to obtain a mixed powder; Step A2: After mixing the thermoplastic styrene-butadiene rubber, modified polystyrene resin and mixed powder at 150-160° C. for 30-40 minutes, adding the modified carbon fiber and plasticizer and continuing mixing for 1-1.5 hours to obtain a rubber material; Step A3: Add the rubber material into the mold, perform compression molding at 150-160° C., and then cool to obtain industrial and mining protective boots.

5. The preparation process of the anti-smashing and anti-smashing industrial and mining protective boots according to claim 4 is characterized in that: The plasticizer in step A2 is one or more of dioctyl phthalate, diethyl phthalate, and dibutyl phthalate mixed in any proportion.

Citation Information

Patent Citations

  • Wear-resistant and high-comfort industrial and mining boot

    CN111700342A